Hubungan mutu pelayanan terhadap minat kunjungan ulang pasien di klinik citra medika kota Semarang - Ahmad Yassir; Purwadhi Purwadhi; Rian Andriani (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
The purpose of this study was to determine the relationship between service quality and patient intention to revisit at the Citra Medika Clinic in Semarang City. This type of research is cross sectional quantitative research. The research population is the average number of patients per month from September 2021 – August 2022 of 1565 patients at the Citra Medika Clinic in Semarang City. The sampling technique used was purposive sampling with a total sample of 50 people. The data analysis technique used was the research instrument test which consisted of validity and reliability tests, the data processing stage which consisted of editing, coding, entry, cleaning, tabulating, data analysis consisting of univariate analysis and bivariate analysis. The results of this study indicate that there is a relationship between reliability (reliability), assurance (guarantee), tangible (physical/direct evidence), empathy (empathy), and responsiveness (responsiveness) to the intention of repeat patient visits at the Citra Medika Clinic in Semarang City.